Indifference as an instrument of power (2014)
Indifference as a response to situationsof horror provoked bywar can serve different functions.It may be an indicator of the needof a refuge to deal with the traumaticevents, a way of denyingresponsibility for those events, or asinister instrument of power aimedat guaranteeing the effectivenessof those who perpetrate violence,neutralizing social responses,and marginalizing potential reactionsfrom the victims. The articlehighlights the resources contributedby psychoanalysis, artistic creation,and, especially, the legitimizingefforts of justice to palliate theiatrogenic effects of indifference.